Making Legal and Enforcement Decisions in the Management of Resources (on the Example of Ukraine) - Hnativ, Oksana; Harasymiv, Oksana; Senyk, Svitlana; Kossak, Volodymyr (P.A. Persona e Amministrazione, 2024)
Most scientific research is focused on certain aspects of resource management in general, and on natural resources management in particular. However, a comprehensive approach to solving these challenging issues requires clarifying the mechanism of making legal and law enforcement decisions in the field of resource management through the prism of the criteria for their adoption. In addition, the concept of “natural resource management” needs to be replaced by the concept of “resource management”. The Aristotelian (dialectical) method became the leading method of this research at each of its stages. The study of the “resources” concept as a system of interconnected elements was carried out using the synergistic method. The axiological method is important for the systematization of approaches to making legal decisions regarding resource management and the development of a general concept of their adoption. When studying the mechanism of making legal and law enforcement decisions, the formal legal method was used as a special research method. Quantitative methods are justifiably criticized. The application of these methods made it possible to define resources as a complete, interdependent system of elements, as well as to define standards for making legal decisions in the field of resource management.